Kenaf bast fiber filter cartridge for removal of heavy metals and dyes in aqueous solution - Ridwan Shamsudin (N/A, 2016)
Kenaf bast fiber filter cartridge for removal of heavy metals and dyes in aqueous solution by Ridwan Shamsudin